cotx = csc2x + cot2x My Attempt: RS: = 1/sin2x + sin2x/cos2x = (cos2x + sin2x) / (sin2x)(cos2x) = (2cos^2x - 1 + 2sinxcosx) / (2sinxcosx + 1 - 2sin^2x) = 2cos^2x - 1 / 1 - 2sin^2x
Follow Math Help Forum on Facebook and Google+
Originally Posted by Macleef cotx = csc2x + cot2x My Attempt: RS: = 1/sin2x + sin2x/cos2x = (cos2x + sin2x) / (sin2x)(cos2x) = (2cos^2x - 1 + 2sinxcosx) / (2sinxcosx + 1 - 2sin^2x) = 2cos^2x - 1 / 1 - 2sin^2x ALWAYS write everything in terms of sin and cos RHS:
Hello, Macleef! By now, you've seen your mistake . . . Prove: . My Attempt: . ← Here! We have: .
View Tag Cloud